Porous Cobalt–Nickel Hydroxide Nanosheets with Active Cobalt Ions for Overall Water Splitting - Wang, Xiao; Li, Zhe; Wu, De‐Yao; Shen, Gu‐Rong; Zou, Chengqin; Feng, Yi; Liu, Hui; Dong, Cun‐Ku; Du, Xi‐Wen (Small (Weinheim an der Bergstrasse, Germany), 2019)
Low‐cost and high‐performance catalysts are of great significance for electrochemical water splitting. Here, it is reported that a laser‐synthesized catalyst, porous Co0.75Ni0.25(OH)2 nanosheets, is highly active for catalyzing overall water splitting. The porous nanosheets exhibit low overpotentials for hydrogen evolution reaction (95 mV@10 mA cm−2) and oxygen evolution reaction (235 mV@10 mA cm−2). As both anode and cathode catalysts, the porous nanosheets achieve a current density of 10 mA cm−2 at an external voltage of 1.56 V, which is much lower than that of commercial Ir/C‐Pt/C couple (1.62 V). Experimental and theoretical investigations reveal that numerous Co3+ ions are generated on the pore wall of nanosheets, and the unique atomic structure around Co3+ ions leads to appropriate electronic structure and adsorption energy of intermediates, thus accelerating hydrogen and oxygen evolution. An ecofriendly technique, laser ablation in liquid, is adopted to produce porous Co0.75Ni0.25(OH)2 nanosheets with numerous Co3+ ions on the pore wall. These Co3+ ions possess moderate adsorption for the intermediates of both hydrogen evolution and oxygen evolution reactions, thus accelerating electrochemical overall water splitting.